Sistem Proteksi Ganda Dengan Menggunakan Algoritma Rivest Shamir Adleman (RSA) dan Elgamal untuk Proses Enkripsi dan Dekripsi - Islamiyah (STMIK KHARISMA Makassar, 2016)
Security and confidentiality are important aspects needed in the exchange of messages over the network/ internet. Cryptographic techniques can be used to provide security protection to the secret message. Development of multiple cryptographic techniques in combination with RSA algorithm for encryption and decryption and ElGamal algorithm for encryption and decryption process is expected to protect the secret message. This research aims to combine RSA and ElGamal cryptography that provides double protection to the secret message in a text. The result of this study is an aplication of cryptografi by using two algorithms that can perform encryption and decryption using the programming language Visual Basic 6.0